FACTORS INFLUENCE THE BEHAVIOR OF BULLYING AT THE STUDENTS OF SMK PGRI 8 MEDAN IN 2015 - Susilawati, Endang; Yahya, Syarif Zen; Simanjuntak, Wenny F (Politeknik Kesehatan Kemetrian Kesehatan Medan, 2015)
Bullying is aggressive behavior intentionally to attack the target or victim in weak position, easy for insulted and can not self defense. The characteristic of children that influence the sensitivity of childrento do the bullying in school. Factors influence the bullying behavior is personality, peers, school climate. This research aims toi study factors influence the bullying behavior at SMK PGRI 8 Medan. The design of this research is descriptive study using cross sectional approach. The population in this research is students of SMK PGRI 8 Medan for the number of 164 students. The sample is take by accidental sampling for the sample is 35 students by the measurement tool is questionnaire. The result of research indicates that factors of personality, peer, and school climate influence the behavior of bullying of anyone. Based  on research,  the dominant factor is school climate and peer. Based on the result of research indicates that the bullying in mild category is 14 respondents (40%), medium is 11 respondents (31,4%) and severe is 10 respondents (28,6%). It is suggested to the student to increase their knowledge about bullying, follow the value and norm applied in school, and develop the empathy, faith on God and build a good communication or relationship to the peer and teacher.